Diversifikasi Kredit, Monitoring dan Kinerja Perbankan di Indonesia - Iin Emy Prastiwi; Anik Anik Anik (ITB AAS INDONESIA Surakarta, 2020)
This study aims to determine the banking credit diversification strategy that can control credit risk and credit diversification can increase the profitability of banks in Indonesia. This study also aims to discuss the role of monitoring in the implementation of diversification and its impact on the performance of Indonesian banks. The theoretical benefits of this research contribute to banks, especially in evaluating banking diversification strategy policies. Is the credit diversification strategy can reduce credit risk and improve banking performance or vice versa. For customers / investors, this research is one of the information that can be considered in choosing a safe bank in terms of the level of credit risk and bank profitability. This research method uses descriptive qualitative analysis. The results of this study indicate that credit diversification is the right strategy applied to banks in Indonesia. The government needs to implement further policies that support the implementation of credit diversification, such as conducting credit analysis, monitoring and evaluation.